THE EFFECT OF PROMOTION AND THE EFFECTIVENESS OF NON-CASH TRANSACTIONS ON THE INCREASE IN KFC CONSUMER PURCHASES IN JAKARTA THROUGH TIKTOK SHOP IN 2025 - Wilson Theodora; Margareth Angelika Widjaya; Clara Kabita; Jason Alexander Wijaya; Kevin Gouw; Tumpal J.R.Sitinjak (Bajang Institute, 2026)
The rapid development of digital technology has transformed marketing strategies and consumer purchasing behavior, particularly through social commerce platforms such as TikTok Shop. This study aims to examine the effect of promotion and the effectiveness of cashless transactions on the increase in consumer purchases of KFC in Jakarta through TikTok Shop. This research employs a quantitative approach using a causal associative method. Primary data were collected through questionnaires distributed to 100 respondents who are KFC consumers in North Jakarta and have made purchases via TikTok Shop. The sampling technique applied was purposive sampling. Data analysis was conducted using multiple linear regression analysis and partial hypothesis testing (t-test) with the assistance of SPSS software. The results indicate that promotion has a positive and significant effect on increasing consumer purchases of KFC through TikTok Shop. Furthermore, the effectiveness of cashless transactions also has a positive and significant influence on the increase in consumer purchases. These findings suggest that promotional strategies in the form of discount vouchers delivered through interactive TikTok Shop content, combined with fast, secure, and convenient cashless payment systems, are effective in stimulating consumer purchase intention and purchase frequency. This study is expected to contribute to the development of digital marketing management literature and provide practical insights for companies in designing more effective promotional strategies and digital payment systems.